2015
DOI: 10.3329/bjb.v43i2.21666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of integrated nutrient management on growth and yield of maize (Zea mays L.) - Gobhi sarson (Brassica napus L.) cropping system in sub-tropical region under foothills of north-west Himalayas

Abstract: A pronounced residual effect of organic and inorganic fertilizers, applied in maize crop was observed on yields of maize-gobhi sarson cropping system. The experiment was conducted with 10 treatments of N, P, K, FYM, crop residue and zinc sulphate nutrients. The highest growth, yield and yield components of maize crop were recorded with 100% recommended fertilizer dose-RFD + ZnSO4 20 kg/ha and the grain yield (2409 kg/ha) was about 101% higher over the control. In case of gobhi sarson, the highest seed yield (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 1 publication
3
9
0
Order By: Relevance
“…Data indicated that combined application of organic and inorganic sources of nutrients in maize significantly influenced total systems phosphorus uptake during both the years with similar trend as that of N uptake. Treatments, receiving higher amounts of fertilizer NPK resulted in higher uptake of P. Similar results were also reported by Gupta et al, (2014) and Sharma et al, (2014). Fertility treatments in wheat also brought about significant variation in systems total P uptake during both the years.…”
Section: Phosphorus Uptake (Kg Ha -1 )supporting
confidence: 89%
“…Data indicated that combined application of organic and inorganic sources of nutrients in maize significantly influenced total systems phosphorus uptake during both the years with similar trend as that of N uptake. Treatments, receiving higher amounts of fertilizer NPK resulted in higher uptake of P. Similar results were also reported by Gupta et al, (2014) and Sharma et al, (2014). Fertility treatments in wheat also brought about significant variation in systems total P uptake during both the years.…”
Section: Phosphorus Uptake (Kg Ha -1 )supporting
confidence: 89%
“…Zaremanesh et al, 2017 also found that the application of vermicompost resulted higher grain yield of maize. Gupta et al, 2014 also reported the higher yield in maize due to integrated application of organics and inorganics source of fertilizer. The higher grain yield with integrated nutrient management treatments might be due to remarkable increase in yield components such Biswasi et al, 2020 as number of grains and grain weight.…”
Section: Grain and Stover Yieldmentioning
confidence: 94%
“…It was reported that long term combined application of zinc, sulfur and along with FYM significantly increased crop yield, uptake and availability of micronutrients in soil over chemical fertilizer alone (Ameta et al, 2014). Researchers (Gupta et al, 2014) also reported that integrated nutrient management increased the economic yield of mustard-based cropping system by 35 % than that without FYM treatment. The present experiment was, therefore, conducted to study the influence of integrated nutrient management (especially FYM, S and Zn) on soil fertility build up as well as yield and quality improvement of rapeseed.…”
Section: Introductionmentioning
confidence: 98%